Cold to the touch - Fyfield, Frances (Sphere, 2010)
Beautiful, volatile Jessica has long since burned her boats in the village by the sea where she was born. She longs to return, but first she needs to secure the love of the powerful man who has spurned her obsessive adoration.Sarah Fortune, her older, cynical friend, is keen to distance herself from her usual haunts and welcomes the chance to leave London in the hope that she might she be able to effect a reconciliation between Jessica and her mother. Pennyvale both charms and distracts her with hints of scandal and buried secrets, but it soon begins to disquiet her as cracks of distrust and jealousy show in the polite facades. Sarah is excited when Jessica tells her she is coming home, but she never arrives. Sarah's instinctive knowledge of Jessica leads her back to the capital, fearful of what she will find. What she discovers reveals a truth more chilling than she could have imagined, but she has to return to Pennyvale to fully understand how Jessica was finally brought home, and why...